The discovery of rest-frame UV colour gradients and a diversity of dust morphologies in bright z ≃ 7 Lyman-break galaxies - Bowler, RAA; Cullen, F; McLure, RJ; Dunlop, JS; Avison, A (Oxford University Press, 2021)
We present deep ALMA dust continuum observations for a sample of luminous (MUV < −22) star-forming galaxies at z ≃ 7. We detect five of the six sources in the far-infrared (FIR), providing key constraints on the obscured star-formation rate (SFR) and the infrared-excess-β (IRX–β) relation without the need for stacking. Despite the galaxies showing blue rest-frame UV slopes (β ≃ −2) we find that 35–75 percent of the total SFR is obscured. We find the IRX–β relation derived for these z ≃ 7 sources is consistent with that found for local star-burst galaxies. Using our relatively high-resolution (FWHM ≃ 0.7 arcsec) observations we identify a diversity of dust morphologies in the sample. We find both compact emission that appears offset relative to the unobscured components and extended dust emission that is co-spatial with the rest-frame UV light. In the majority of the sources we detect strong rest-frame UV colour gradients (with up to Δβ ≃ 0.7–1.4) as probed by the multi-band UltraVISTA ground-based data. The observed redder colours are spatially correlated with the location of the FIR detection. Our results show that even in bright Lyman-break galaxies at z ≃ 7 the peak of the star-formation is typically hosted by the fainter, redder, regions in the rest-frame UV, which have an obscured fraction of fobs ≥ 0.8. As well as demonstrating the importance of dust obscured star-formation within the Epoch of Reionization, these observations provide an exciting taster of the rich spatially resolved datasets that will be obtained from JWST and high-resolution ALMA follow-up at these redshifts.